Neutrophils in the bone marrow express DEC205, guiding their migration to inflamed tissues - Jin, Shiying; Lei, Xuan; Singh, Sonali; Enk, Alexander; Mahnke, Karsten (Immunology, 2025)
The surface molecule DEC205 (CD205) is well-characterised in murine dendritic cells (DCs) as an antigen uptake receptor. However, recent studies have also identified its expression in other leukocytes, including B cells and neutrophils. In B cells, DEC205 functions as an endocytic receptor, similar to its role in DCs. Since neutrophils are not professional antigen-presenting cells, we sought to investigate the functions of DEC205 beyond endocytosis. Analysis of cell surface expression of DEC205 in neutrophils at different maturation stages and anatomical locations revealed its downregulation upon in vitro activation and during tissue infiltration, such as in skin inflammation and thioglycolate-induced peritonitis. In DEC205-deficient (DEC205−/−) mice, neutrophils exhibited reduced migration in Boyden chamber assays and impaired accumulation in the peritoneum, along with decreased adhesion to extracellular matrix proteins. These findings suggest that, beyond its established role as an antigen uptake receptor in antigen-presenting cells, DEC205 may serve as a marker for early-stage neutrophils with the capacity to migrate and infiltrate tissues.